Machines à penser. - Roelstraete, Dieter; Basar, Shumon; Riley, Mark; Wittgenstein, L.; Adorno, Theodor W.; Heidegger, Martin (Milaan : Fondazione Prada, 2018)
Finlay, I Hamilton ; Kluge, A. ; Richter, G. ; Semah, J. ; Nys, S. ; Philipsz, S. ; Kiefer, A. ; Chiasera, P. ; Machuga, Goshka, Antunes, Leonor
Adorno, Heidegger, Wittgenstein, Weimar on the Pacific, Heidegger's Hut, Hutopia
Machines à penser, Fondazione Prada, Venetië, 26 mei tot 26 november 2018
boek